Synthesis and characterization of zinc derivatized 3, 5-dihydroxy 4′, 7-dimethoxyflavone and its anti leishmaniasis activity against Leishmania donovani - Gupta M.K.; Chiranjivi A.K.; Dutta T.; Dubey V.K.; Rangan L. (My University, 2025)
This study reports the synthesis and characterization of zinc derivatized 3,5-dihydroxy 4′, 7- dimethoxyflavone (DHDM-Zn) compound for the development of new antileishmanial agents. The interaction studies of DHDM with zinc were carried out by UV spectra and fluorescence spectra analysis. Characterization of the complex was further accomplished by multi-spectroscopic techniques such as FTIR, Raman, HRMS, NMR, FESEM-EDX. The morphological and topographical studies of synthesized DHDM-Zn were carried out using FESEM with EDX. Further, it was demonstrated that DHDM-Zn exhibited an excellent in vitro antagonistic effect against the promastigote form of L. donovani. In addition, the possible mechanisms of promastigote L. donovani cell death, by involvement of derivatized compound in arrest of the cell cycle in the G1 phase and residual cell count reduction were investigated. Promastigote growth kinetics performed in the presence of the derivatized compound revealed a slow growth rate. The combination of growth kinetics and cell cycle analysis, made it possible to interpret and classify the cause of leishmanial cell death accurately. These results support that zinc derivatized complex (DHDM-Zn) might work as a lead compound for designing and developing a new antileishmanial drug. Graphical abstract: [Figure not available: see fulltext.]. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.